Greenhouse effect : Climate control and global warming - Rees, Rod.; Leslie, Cath.; Rees Films; Video Education America (Thornwood, NY : VEA (Video Education America), 2007)
Explains the science of greenhouse effect and the evidence that we are causing climate change. The DVD contains an advanced version for senior students, with in-depth analysis of greenhouse gases and their effects. Extra segments include ice core research in Antarctica, how warming threatens coral reefs, and how carbon capture and storage work.
Basic version (suitable for all levels) (22 min.) -- Advanced version (more analysis of greeenhouse gases) (25 min.) -- Extras.
Narrator: Cath Leslie.
Digital video disc.
System requirements
No Master.
Keywords: Global warming; Greenhouse effect, Atmospheric; Climatic changes